Effect of green mussel (Perna Veridis) shell powder as partial fine aggregate replacement on the mechanical properties of concrete - Nagor Maidin, M M; Othman, N H; Sulaiman, N; Sainudin, M S; Abdul Hamid, N A; S Ayop, S (2023)
Depletion of natural resources is one of sustainability problem which requirement to address in efficiently. Nowadays, the trend in construction industry is to use the alternative source of construction materials which can substitute the use of new materials. The aim of this attempts is to reduce environmental impact in terms of energy consumption, pollution, waste disposal and global warming. As an alternative solution to reduce waste quantity by utilizing it in construction materials. Thus, this study was carried out to identify the physical properties of the mussel shell powder as partial fine aggregate replacement and to define the optimum percentage of mussel shell powder in concrete based on its physical and mechanical properties. The percentage of mussel shells powder used in this study were 0%, 10%, 20% and 30% (C100, C10MSP, C20MSP and C30MSP). The total 48 cubes sample size, 100mm x 100mm x 100mm were used and tested on its compressive strength and capillary water absorption test for 7 and 28 curing days. The result shows that specific gravity of fine aggregate is lower than mussel shells powder which was 2.76 and 2.90. Based on compressive strength resulted, C20MSP has high strength (35.9 MPa) compare to another concrete mixes. While for the water capillary absorption resulted that C30MSP has the low average water capillary absorption (0.12cm/s). Therefore, for the mechanical properties of this research, it can be concluded that mussel shell replacement should be in average between 20% to 30% of fine aggregates. Furthermore, the high content of calcium carbonate (CaCO3) in chemical composition of mussel shell powder act as a filler in concrete and promoting early hydration process